Psychological Characteristics and Predictors of Suicide Probability in High-Risk Prisoners - Gooding, Patricia A. (Criminal justice and behavior, 2017)
Suicidal thoughts and behaviors are highly prevalent in prisoners. Nevertheless, there have been scant attempts to understand suicidality in prisoners from a psychological perspective. The goals of this study were to characterize a prison sample at high risk of suicide in terms of hopelessness, defeat, and entrapment, and to determine which of these variables predicted suicidality. A cross-sectional questionnaire design was used. Measures of hopelessness, defeat, entrapment, and suicide probability were administered to male prison inmates in the United Kingdom. Defeat and hopelessness, especially the affective component of hopelessness, predicted the probability of suicide in this sample, but entrapment was not a significant predictor. Suicide risk assessment procedures in prisons tend to be sparse. Such procedures would benefit from using measures of hopelessness and defeat. Future work should aim to understand how the impact of these psychological constructs on suicidality in prisoners can be attenuated.